Antioxidant properties and antimicrobial activity of selenium nanoparticles synthetized via Zambian medicinal herbs - Pompido Chilala; Monika Jurickova; Zuzana Pokorna; Tereza Motlova; Pavel Horky; Sylvie Skalickova (PLoS ONE, 2025)
Previous studies of green synthesized selenium nanoparticles (SeNPs) showed their unique properties such as antibacterial activity, biocompatibility, and antioxidant properties. This study aimed to use traditional Zambian medicinal herbs (Azadirachta indica, Moringa oleifera Gliricidia sepium, Cissus quadrangularis, Aloe barbadensis, Kigelia Africana, and Bobgunnia madagascariensis) to synthesize SeNPs and examine their potential to enhance the endogenous antioxidant system of model eukaryote. For SeNP characterization, dynamic light scattering, scanning electron microscopy, Fourier transform infrared spectroscopy,and absorbance spectra were used. Their minimal inhibitory concentration was investigated on Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) bacteria. The antioxidant potential of SeNPs was examined on Saccharomyces cerevisiae (S. cerevisiae). Cell viability, total antioxidant capacity, and activity of superoxide dismutase, catalase, and glutathione peroxidase were evaluated. SeNPs did not show antimicrobial activity against E. coli, only mild activity against S. aureus. Experimental data suggested that SeNPs didn´t inhibit Saccharomyces cerevisiae growth while plant extracts and sodium selenite had an inhibitory effect. All tested plant extracts and SeNPs resulted in a significant decrease in superoxide dismutase activity compared to the control. Catalase activity significantly increased only in treatments with plant extracts or sodium selenite alone. Glutathione peroxidase activity remained the same for all studied SeNPs and plant extracts. These findings provide evidence of a complex influence of SeNPs or plant extracts on the cellular antioxidant system in S. cerevisiae. From the point of view of overall effectiveness, Azadirachta indica, Moringa oleifera, Aloe barbadensis, and Cissus quadrangularis SeNPs are promising, green-synthetized nanoparticles for combating oxidative stress in living organisms.